EXPERIENCES OF GRANDPARENTS RAISING GRANDCHILDREN IN MALAWI. (11th November 2018) - Lee, Y; Blitz, L
Abstract: In Malawi, 16% of children have been orphaned and many are being raised by grandparents. Considering the complex nature of the caregiving and the significant contribution grandparents raising grandchildren make to the community, it is important to explore their experiences and unique strengths and needs. Using a case study approach, seven focus groups were conducted with 29 custodial grandparents in three Malawian villages in 2017. The mean age of the grandparents was 62 years old (range: 45–80) and they were raising 3.2 grandchildren (range: 1–8) for 9 years (range: 3–18) on average; only one was a grandfather. Causes of the death of parents of the grandchildren include: HIV (ten); Tuberculosis (eight); Cancer (three); Asthma (one); killed on the road (one); and unknown reasons (five). Thematic analysis as an inductive and data driven approach generated six major themes: (1) finding meaning in giving grandchildren a better future; (2) importance of the family circle; (3) strong support from other grandparents and the community; (4) financial and physical hardships; (5) intrafamilial and intergenerational conflicts; and (6) desire for more involvement with their grandchildren's education and schools. The findings point to complex intersections of trauma, loss, stress, community support, and resiliency. Understanding these intersections can promote effective family and community engagement which will facilitate the role of schools in addressing complex social-emotional and developmental issues with children and youth in Malawi. Findings also inform understanding and work with custodial grandparents in the U.S. and other parts of the world.